Determinants of SMES Voluntary Tax Compliance: Moderated by Tax Knowledge Requirement - Suryanto, Beni; Krisnanto, Krisnanto; Komara, Acep; Syifaudin, Ahmad (DINASTI RESEARCH, 2025)
This study investigates the factors influencing voluntary tax compliance among Micro, Small, and Medium Enterprises (MSME) in Cirebon and Kuningan, with a particular focus on perceived procedural fairness and service quality, moderated by tax knowledge. Employing a quantitative approach, data were collected from 103 MSME taxpayers using stratified random sampling and analyzed through moderated regression analysis (MRA) and subgroup analysis. The findings reveal that perceived procedural justice significantly enhances voluntary tax compliance, while service quality does not show a significant effect. Tax knowledge functions as a quasi-moderator, reinforcing the positive relationship between procedural justice and compliance, but it does not moderate the effect of service quality. These results support the Extended Slippery Slope Framework and the Theory of Planned Behaviour, both of which highlight the roles of fairness and taxpayer education in fostering compliance. The study recommends that tax authorities enhance procedural transparency and develop tax education programs for MSME. However, the limited geographic focus on Cirebon and Kuningan represents a constraint, suggesting the need for broader research in future studies.